Paper waste sludge enhanced eco‐efficient polyurethane foam composites: Physical–mechanical properties and microstructure. Issue 6 (6th July 2016) - Kairytė, Agnė; Kirpluks, Mikelis; Ivdre, Aiga; Cabulis, Ugis; Vėjelis, Sigitas; Balčiūnas, Giedrius
Abstract : Increasing demands and consumption of humankind make an increase in paper production, extending the accumulation of paper production wastes. Due to legislations pertaining to environmental pollution, it has become necessary to search for new areas where these wastes could be used. Some of the processes such as milling, purification, etc. of fillers in the production of building materials are expensive and their cost reduction is desirable; therefore, the objective of this research is to develop strong and multifunctional rigid polyurethane foam composites from bio‐based polyol that are filled with unpurified and high distribution in size, having paper waste sludge (PWS) particles, and to investigate the possibility to recycle them as filler in polyurethane composites. The rational amount of PWS particles is 5% by foam mass. PWS particles improve thermal conductivity, water vapor resistance, density, compressive strength, and modulus of elasticity as compared to neat polyurethane foam matrix. POLYM. COMPOS., 39:1852–1860, 2018. © 2016 Society of Plastics Engineers